2021
DOI: 10.21273/hortsci15412-20
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Postzygotic Barriers Associated with Intergeneric Hybridization between Aronia melanocarpa (Michx.) Elliott x Pyrus communis L. and ×Sorbaronia dippelii (Zabel) CK Schneid. x Pyrus communis

Abstract: Intergeneric hybridization between Aronia and Pyrus may provide a pathway for developing novel fruit types with larger, sweeter fruits, while maintaining the high levels of biologically health-promoting compounds present in Aronia fruits. Here we describe a deleterious genetic incompatibility, known as hybrid necrosis or hybrid lethality, that occurs in intergeneric F1 hybrids of Aronia melanocarpa x Pyrus communis and ×Sorbaronia dippelii x Pyrus communis. Pollination experiments revealed that maternal A. mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The current Maleae tribe consists of at least 500 species in over 30 genera (Xiang et al, 2017), but the development of intergeneric hybrids has only been reported for a few cross-combinations (Postman, 2011). Additionally, although cross-compatibility across some Maleae genus and species has been partially clarified on the basis of fruit set and in vivo pollen tube growth (Mahoney and Brand, 2021;Yang and Fu, 2020), classification of, and behavior in, cross-incompatibility remain to be investigated across a wide range of combinations.…”
Section: Introductionmentioning
confidence: 99%
“…The current Maleae tribe consists of at least 500 species in over 30 genera (Xiang et al, 2017), but the development of intergeneric hybrids has only been reported for a few cross-combinations (Postman, 2011). Additionally, although cross-compatibility across some Maleae genus and species has been partially clarified on the basis of fruit set and in vivo pollen tube growth (Mahoney and Brand, 2021;Yang and Fu, 2020), classification of, and behavior in, cross-incompatibility remain to be investigated across a wide range of combinations.…”
Section: Introductionmentioning
confidence: 99%